Komunikasi Pernikahan Beda Budaya (Studi Komunikasi Antarpribadi Pasangan Arab Alawiyyin dan Non-Alawiyyin di Kampung Arab Solo, Jawa Tengah) - Caecilia Menzelthe (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2022)
This study aims to find out how the processes, communication barriers, and adaptations carried out by different cultural couples between Arab Alawiyyin and Non-Arab Alawiyyin in their married life. Communication is the main key in a marriage. Especially in a marriage between two people with different cultural backgrounds, interpersonal communication is important to achieve harmony in a family. This research is a phenomenological study that aims to determine the subjective experience of interpersonal communication between Alawiyyin and non-Alawiyyin Arab marriage couples. The results showed that interpersonal communication between Alawiyyin and non-Alawiyyin Arab couples took place harmoniously because of adjustments made before and during the marriage period. Commitments and agreements are made and negotiated with effective communication between the two. Communication barriers in general can be overcome well, even though at the beginning of marriage it was the toughest moment for couples to adjust. Differences in culture, customs, norms and values between partners are other factors that hinder communication. Openness, empathy, mindfulness, cultural sensitivity, and other effective interpersonal communication skills are keys to success in intercultural marriage relationships. In addition, the extended family and its values are the main factors that must be compromised, especially in the early moments of marriage.